C.2 - Prasad, K. N. (New Delhi, 1984)
Economic terms and concepts are crystallizations of important thoughts. Systems of economic analysis and systems of economic thought are integrated wholes. Acquaintance with the history of ideas ensures a better appreciation of the significance of the present-day theories. The studies contained in this book are critical introductions to the development of the leading economic ideas and theories like nature and significance of economic science, methods of explanation in social, in comparison to, natural sciences, production functions, factors of production as economic and social concepts, nature of factorial rewards, demand-and supply analysis, integration of value and distribution as well as of pro duction and distribution theories, marginal productivity theory, theories of rent, wages, interest, and profit, role of economic theory in policy-making, economic policy and alleviation of the poverty problem, etc. An attempt has been made to restate and evaluate the contributions of the individual economists of the classical, neo-classical, and modern (neo-Keynesian and neo-classical) periods to the emergence of the existing economic doctrines from different vantage points. This is the author's forté. In this work he has handled the themes with clarity and persuasiveness, care and accuracy, deftness and lucidity of exposition and, finally, with due attention to detail. This publication should enable the students, research scholars and teachers of economics and other social sciences to understand the issues covered better, whether the purpose is learning, teaching or research. It should prove useful also to the general readers with proper grounding in economics.
Keywords: Economic policy